1993
DOI: 10.1111/j.1439-0396.1993.tb00317.x
|View full text |Cite
|
Sign up to set email alerts
|

Auswirkungen von Zinkmangel und der Applikation von rekombinantem bovinem Wachstumshormon auf Wachstumshormon und IGF‐1 im Plasma von Kälbern

Abstract: Zusammenfassung Ein 15wöchiger Aufzuchtversuch und ein 10wöchiger Mastversuch mit 4times12 männlichen Braunviehkälbern wurde durchgeführt, um den Einfluß einer mangelnden Zinkversorgung und der Applikation von exogenem bovinem Wachstumshormon auf die Konzentrationen von Wachstumshormon und IGF‐1 im Plasma von Kälbern zu untersuchen. Dazu wurde den Mangeltieren des Aufzuchtversuches zusätzlich zu einem Kraftfutter (7,8 mg Zink/kg Futter) bis zur 7. Woche ein halbsynthetisches Milchaustauschfutter (6,7 mg Zink/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
2
1
0
Order By: Relevance
“…However, in the study described here the concentration of IGF-1 in the serum of the Zn-deficient rats was reduced by a significant 28% despite elevated GH levels. Reduced IGF-1 concentrations in Zn deficiency were also unanimously reported by other authors in animals {Cossack 1984;1986;Oner, Bhaumick and Bala 1984;Bolze, Reeves, Lindbeck and Elders 1987;Dorup et al 1991;Heindl et al 1993;Dicks, Rojhani and Cossack 1993;Droke et al 1993) and in humans {Ghavami- Maibodi et al 1983;Cossack 1991;Nakamura, Nishiyama, Futagaishi-Suginohara, Matsuda and Higashi 1993), which were reversible following Zn repletion {Cossack 1984;1986;1988;Ghavami-Maibodi et al 1983;Bolze et al 1987;Nishi et al 1989). The cause of the reduced IGF-1 levels in Zn deficiency while GH concentrations in the serum are elevated is believed to be an impairment of the stimulating effect of GH on IGF-1 synthesis.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…However, in the study described here the concentration of IGF-1 in the serum of the Zn-deficient rats was reduced by a significant 28% despite elevated GH levels. Reduced IGF-1 concentrations in Zn deficiency were also unanimously reported by other authors in animals {Cossack 1984;1986;Oner, Bhaumick and Bala 1984;Bolze, Reeves, Lindbeck and Elders 1987;Dorup et al 1991;Heindl et al 1993;Dicks, Rojhani and Cossack 1993;Droke et al 1993) and in humans {Ghavami- Maibodi et al 1983;Cossack 1991;Nakamura, Nishiyama, Futagaishi-Suginohara, Matsuda and Higashi 1993), which were reversible following Zn repletion {Cossack 1984;1986;1988;Ghavami-Maibodi et al 1983;Bolze et al 1987;Nishi et al 1989). The cause of the reduced IGF-1 levels in Zn deficiency while GH concentrations in the serum are elevated is believed to be an impairment of the stimulating effect of GH on IGF-1 synthesis.…”
Section: Discussionsupporting
confidence: 71%
“…As the experiment progresses and the severity of the Zn deficiency increases, this can ultimately also lead to a reduction in the concentration of growth hormone in the serum. This would also explain the apparent contradictions in the literature, according to which prolonged and severe Zn deficiency led to reduced serum GH concentrations {Root et al 1979;Collipp, Castro-Magana, Petrovic, Thomas, Cheruvansky, Chen and Sussman 1982;Kirchgefiner and Roth 1985) or unchanged GH levels {Dorup, Flyvbjerg, Everts and Clausen 1991;Droke, Spears, Armstrong, Kegley and Simpson 1993;Heindl, Kirchgefiner and Schams 1993) and even, as in the study described here, to an increase in the serum GH concentration after a relatively brief 11-day period of Zn depletion. Droke et al (1993) also reported higher serum GH concentrations following application of GH releasing factor in Zn-deficient lambs.…”
Section: Discussionsupporting
confidence: 43%
“…Growth hormone (GH) is a growth promoter in several animal species (HART and JOHNSOI\I, 1986;GLUCKMAN et al, 1987), including calves (KIRCHGESSNER et al, 1987). It is well-known that secretion, metabolism and effects of G H and insulin-like growth factor I (IGF-I) are dependent on nutritional status, especially energy and protein intak.e (PHILLIPS and UNTERMAN, 1984;BLUM et al, 1985;BREIER et al 1986;UNDERWOOD et al, 1986;RONGE and BLUM, 1989a;PELL and BATES, 1990;THISSEN et al, 1994) and modified by other nutritional factors such as zinc intake (HEINDL et al, 1993). hletabolic rate is reduced in Fe deficiency anaemia (DALLMAN, 1986), as also demonstrated in calves based on decreased oxygen consumption before and during physical performance (LINDT and BLUM, 1993;PIGUET et al, 1993).…”
Section: Introductionmentioning
confidence: 99%